Transtornos alimentares: estudos de casos na Terapia Ocupacional em saúde mental - REIS, Brenda Caroline Cardoso (2023)
Eating disorders, such as anorexia, bulimia and pica disorder, are characterized by a disruption in food and / or behavior related to it, resulting in altered food consumption, compromising physical health or psychosocial functioning. Thus, people with mental disorders, among them, people with eating disorders may have their engagement in the affected occupations and consequently, they start to face prejudices and lack of opportunities, further inhibiting their participation in occupations. In this perspective, the occupational therapist as one of the professionals who work in mental health aims at the autonomy and reinsertion of this user in the family and in the community, and can contribute in a significant way in the treatment of people with eating disorder. Based on these aspects, this research aims to understand aspects of the mental health of people with eating disorders under the occupational therapy optics. These are two case studies of quantitative and qualitative descriptive character. The subjects of the research were two people, codenames Rosa and Margarida, with diagnosis or diagnostic impressions of Eating Disorder; Young adults between 22 and 26 years of age; female; Who agreed to participate in the research, signing the Term of Free and Informed Consent TCLE. The research instruments applied were: Mental State Assessment Form, EAT26 Questionnaire (Rosa only) and Occupational Therapeutic Intervention Plan, individually, applied at the Faculty of Physical Therapy and Occupational Therapy (FFTO), Federal University of Pará (UFPA). It could be noted that the interviewees present compromises in the aspects: critical judgment and conduct, because for both, the search for treatment is irrelevant, and the possible treatments for eating disorders are not effective. In addition, they believe that the consequences of TA are not aggravating. When questioned about communicating to their families and friends about the TA, the interviewees affirmed the omission, being explained in the Rosa case, for fear of repression by the closest people and in the case Margarida, because it is an unnecessary subject to be discussed or communicated. In both cases of eating disorders, it was noted that dissatisfaction with body image is associated with age, and, consequently, the risk of developing BP. The researchers were able to achieve the objectives and understood the mental health aspects of people with eating disorders from the occupational therapy perspective. In addition, they identified the impaired aspects and developed an Occupational Therapeutic Intervention Plan to minimize changes in such aspects. It is concluded that occupational therapeutical interventions in eating disorders, especially those related to this study (anorexia, bulimia and pica disorder), can provide awareness of the disorders caused by the disorders and work mainly on aspects such as critical judgment, Conduct and body image, aiming to improve the quality of life.